Investigating the Role of Imaging Modalities, Such as Computed Tomography (CT) or Magnetic Resonance Imaging (MRI), in the Diagnosis and Management of Temporal Bone Disorders - Aftab Ahmad, Fazal Rehman, Asghar Ullah Khan, Javed Iqbal, Arshad Abbas, Kamran Chaudhry (Pakistan Journal of Medical & Health Sciences, 2025)
Aim and Objective: The aim of the study was to assess the role of tomography (CT) or magnetic resonance imaging (MRI), in the diagnosis and management of temporal bone disorders. Materials and Method: The current prospective study was conducted at the Department of ENT from April 2022 to September 2022 after approval from the institutional review board. A total of 60 patients were included in the study selected through the purposive sampling technique. The age of the participants was up to 75 years. Informed consent was obtained from each patient. All the data was collected from the lab reports and the results of the CT scan and MRI done for each individual and then analyzed by using the latest version of SPSS 24. Results: A total of 60 participants were selected on the basis of their symptoms which include both males and females. 28.33 % of them were from 21-30 years of age and 25 % of them were 31-40 years of age. 41-50 years of age were 15 %. 37 (61.66 %) of them were male and 23 (38.33 %) were female participants. overall, 13.33 % of them had fractured the temporal bone, The most common of them had mastoiditis 31.66 %, 21.66 % had cholesteatoma and 3.33 % of them had otitis externa. 5 % had meningioma. 9 (45 %) had meningitis, 15 % had brain abscesses, and 25 % of them had carotid canal irregularity. Conclusion: The current study concluded that both CT scans and MRIs have a vital role in accurately diagnosing the various types of temporal bone disorders like mastoiditis, cholesteatoma, bone fractures, and congenital malformations which helps us to treat and manage the patients according to their etiology. Therefore, CT scans and MRIs have a key role in investigating and managing patients properly. Keywords: Cholesteatoma, mastoiditis, temporal bone disorder, CT scan, MR